PERBEDAAN KOMITMEN ORGANISASI, BEBAN KERJA, DAN IKLIM ORGANISASI TERHADAP STRES KERJA - Sri Kubillawati; Carwadi; Najah Putri Nafa (JURNAL KESEHATAN DAN KEBIDANAN, 2022)
Job stress is a psychosocial hazard that comes from various sources, such as work organization, work design, working conditions and co-worker relationships. This will be a risk in occupational health and safety as well as one of the problems that are often experienced in various parts of the world. Currently, work stress has become a global issue that greatly affects all professions, both in developed and developing countries. Job stress is a factor that causes employees to be depressed, bored, and feel uncomfortable conditions in working at the company1 This study aims to determine differences in work stress on organizational commitment, workload and organizational climate among workers at PT. Ikhtiar Mulia Construction in 2021. This research is quantitative in nature, using analytical descriptive method with a cross-sectional approach. This study uses primary data by providing a questionnaire. The sample that will be used as the object of research is all workers at PT. Ikhtiar Mulia Konstruksi in 2021 as many as 60 workers. The results of the study stated that there was a significant difference in work stress based on workload, and there was no significant difference in organizational commitment, organizational climate based on work stress at PT. Ikhtiar Mulia Konstruksi in 2021. To reduce the number of workers who experience work stress on the workload, the company is advised to increase the number of workers to reduce the workload and the work can be completed on time.